Efficacy of the cooling method for targeted temperature management in post-cardiac arrest patients: A systematic review and meta-analysis. (1st March 2020) - Kim, Jae Guk; Ahn, Chiwon; Shin, Hyungoo; Kim, Wonhee; Lim, Tae Ho; Jang, Bo-Hyoung; Cho, Youngsuk; Choi, Kyu-Sun; Lee, Juncheol; Na, Min Kyun
Abstract: Objective: This review aimed to compare the efficacy of endovascular cooling devices (ECD), such as Thermogard®, with surface cooling devices (SCD), such as Arctic Sun®, in reducing mortality and improving neurological status for patients with post-cardiac arrest undergoing targeted temperature management. Data sources: A systematic literature search was conducted using MEDLINE, EMBASE, and the Cochrane Library to identify randomized controlled trials (RCT) and observational studies (OS) comparing mortality and neurological status for patients treated with ECD or SCD. Results: The meta-analysis comprised 4, 401 patients from 2 RCT and 7 OS. For mortality, the overall pooled analysis showed no statistically significant difference between ECD and SCD recipients (RR, 0.93; 95% CI 0.86–1.00; I 2 = 0%). Further, no statistically significant difference was observed between RCT (RR, 0.80; 95% CI 0.56–1.14; I 2 = 0%) and OS (RR, 0.94; 95% CI 0.85–1.04; I 2 = 18%) for in-hospital mortality. For good neurological status of survivors after TTM, the overall pooled analysis showed no statistically significant difference between ECD and SCD (RR, 1.08; 95% CI 0.99–1.18; I 2 = 71%). No statistically significant difference was found between ECD and SCD at hospital discharge in RCT (RR, 0.88; 95% CI 0.61–1.28; I 2 = 0%) and at 6 months in OS (RR, 1.03; 95% CI 0.99–1.09; I 2 = 32%). Conclusions: The study findings could not show that either ECD or SCD was more effective in terms of survival and improved neurological status for post-cardiac arrest patients. Systematic review registration number: CRD42019129770.